2020
DOI: 10.1021/acsomega.0c02967
|View full text |Cite
|
Sign up to set email alerts
|

Development of pH-Controlled Aluminum-Based Polymeric Gel for Conformance Control in Sour Gas Reservoirs

Abstract: Excessive water production from natural gas reservoirs is a main challenge facing the industry nowadays. Polymeric gelants have been widely applied to seal the water production zones, leading to a more feasible production operation. Nevertheless, conventional treatments fail in reservoirs characterized with the presence of sour gases. In this paper, aluminum-based salts are investigated as potential replacement for the conventional chromium acetate as crosslinkers for polyacrylamide (PAM), where aluminum has t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…Particles used for conformance control can be classified into inorganic and organic types in terms of their components. 32 Conventional inorganic particles include but are not limited to coal ash, lime sludge, nutshell, and the combination of calcium clay and cement. 33 Those commercial materials can be acquired from extensive sources.…”
Section: Introductionmentioning
confidence: 99%
“…Particles used for conformance control can be classified into inorganic and organic types in terms of their components. 32 Conventional inorganic particles include but are not limited to coal ash, lime sludge, nutshell, and the combination of calcium clay and cement. 33 Those commercial materials can be acquired from extensive sources.…”
Section: Introductionmentioning
confidence: 99%
“…Shamlooh et al [ 40 ] evaluated the use of different aluminum-based crosslinkers with polyacrylamide systems for the potential use for sour gas conformance control. Four ligands associated with aluminum, namely acetate, amino-acetate, nitrate, and lactate, were tested.…”
Section: Polymer Gel Systemsmentioning
confidence: 99%
“…Results showed that the reduction of the gas relative permeability could achieve 99%. Other metal ions also studied, such as boron, aluminum, , and zirconium, have been put forward and applied in recent years. Hild and Wackowski reported that HPAM-chromic acetate gels were successfully applied in the CO 2 flood project in the Rangely Formation in Colorado.…”
Section: Sealant Materials For Co2 Leakage Controlmentioning
confidence: 99%